Analysis of the Aboriginal Education Policy (New South Wales Department of School Education, 1996) - Hogan, Jessica (The Australian Journal of Indigenous Education, 2000)
The Aboriginal Education Policy (AEP) (New South Wales Department of School Education [NSW DSE], 1996) attempts to create a holistic approach to Aboriginal education for all students. This is done through emphasis on Aboriginal community involvement and incorporating Aboriginal content and perspectives in all stages of schooling. The policy is based on principles which express Aboriginal students' entitlement to the opportunities and understandings which come from education (NSW DSE, 1996: 8). The assumptions and values of the NSW DSE are shown by the emphasis placed on particular aspects of Aboriginal education. The practical impUcations of this policy are that teachers need to become more aware of Indigenous issues, and develop empathy for the past and continuing effects of colonisation.